Рекреації військових та інших вразливих верств населення засобами фізичних вправ - Лаврентьєв, Олександр Миколайович; Крупеня, Світлана Василівна; Деркач, Оксана Вікторівна; Ковальов, В.О.; Криворотько, Юрій Анатолійович; Олександр Лаврентьєв; Світлана Крупеня (Національний педагогічний університет імені М. П. Драгоманова, 2024)
Виходячи з умов сьогодення виникають питання, щодо повернення різних категорій населення (військових, постраждалих, дітей)на відтворення і збереження професійних здібностей та вмінь, використовуючи засоби фізичних вправ або прикладні види спорту, в залежності від ступеня травми пошкоджень (поранень). Так завдяки прикладним видам спорту можна формувати рекреаційну складову, яка має бути легкодоступною та проводитись у формі гри або розваги, направлених на розвиток когнітивних здібностей та сенсомоторних функцій. Також виконання фізичних навантажень на лоні природи і мати декілька напрямів роботи це: звичайні піші походи або походи за складними маршрутами, біг по пересічній місцевості (шосе, ліс та лісопарки), стрибки, спортивна ходьба, розпалення вогнища, розбиття наметів, орієнтування на місцевості, тощо. Навантаження корегується за вказівками та рекомендаціями інструктора ЛФК, адаптуючи хворого до повноцінного життя.

Based on the conditions of the present, questions arise regarding the return of various categories of the population (military, victims, children) to the reproduction and preservation of professional abilities and skills, using physical exercises or applied sports, depending on the degree of injury to injuries (wounds). Thus, thanks to applied sports, it is possible to form a recreational component, which should be easily accessible and conducte d in the form of a game or entertainment aimed at developing cognitive bilities and sensorimotor functions. Also perform physical activities in the bosom of nature and have several areas of work is: the usual Hiking or Hiking on difficult routes, cross-country running (highway, forest and forest parks), jumping, walking, lighting a fire, breaking tents, terrain orientation, etc.. The load is adjusted according to the instructions and recommendations of the exercise therapy instructor, adapting the patient to a fulllife. The author's team [2] proposed a model for the formation of recreational exercises of a sports and applied nature. They successfully combine physical and mental stress against the background of positive emotions in constantly changing external conditions. The development of a course of rehabilitation or recreation can be adapted to different groups of the population, a ccording to the level of their damage, psychological problems or other abnormal everyday situations. Since recreation is the restoration or reproduction of physical and spiritual forces spent by a person in the process of life, which includes a variety of activities in his spare time, aimed at restoring strength and satisfying a wide range of personal and social needs and needs. Therefore, we have expanded the concept of recreational components, which, according to the authors, have a wider range of goals that, according to the specifics, reveal the concepts of both active and passive leisure. Each type of recreation can be applied to a different category of people. What can be regulated by the load mode, applied value, therapeutic orientation, etc. Each type of recreation reveals a wide aspect of the meaning of the direction of activity.
Keywords: населення; травма; поранення; фізичні навантаження; фізичні вправи; прикладні види спорту; відновлювання; population; trauma; injury; physical load; physical exercises; applied sports; recovery